Reflector-based Broadband Antennas offering low profile - Malhotra, Sambhav; Irnstorfer, Florian; Fischer, Georg (Swedish Microwave Days 2023, 2023)
Broadband antennas offering low profile are becoming increasingly important as they provide devices with improved support for multiple frequency bands. A broadband antenna has a large bandwidth (one octave or higher), making them ideal for various technologies such as cellular, Wi-Fi, Bluetooth and navigation. Broadband antennas also reduce the number of antennas required in a single housing, ,by replacing multiple narrowband antennas with a single broadband antenna. Our work focuses on a subset of FR-1 frequency range [1] which goes from 600 MHz to 5 GHz, which covers cellular bands as well as Wi-Fi, Bluetooth and GPS.<br
Keywords: Broadband Antennas; spiral antenna; self complementary antennas; low profile